Encyclopedia of modern Asia - Levinson, David, 1947-; Christensen, Karen, 1957- (New York : Charles Scribner's Sons, 2002)
'Intended for students and non-specialists, this six-volume set does an outstanding job of covering all aspects of modern Asia (economics, religion, technology, politics, education, the arts, environmental issues, international relations, and scientific advances). Recognizing that there is not one Asian culture but many, the editors have been careful to stress both the interrelatedness and the tremendous variance of traditions. The set is equally useful for those researching common themes across Asian culture and those examining a particular country. Well illustrated and carefully indexed, the set is highly recommended for all public and academic libraries.'--'The Best of the Best Reference Sources,' American Libraries, May 2003
volume 1. Abacus to China - volume 2. China-India relations to Hyogo - volume 3. Iaido to Malay-Indonesian language - volume 4. Malaysia to Portuguese in Southeast Asia - volume 5. Possession to Turkey - volume 6. Turkic languages to Zuo Zongtang
Includes bibliographical references and index
Keywords: Asia -- Encyclopedias